Learning the Impact of Financial Education When Take-Up Is Low - Lara Ibarra, Gabriel; McKenzie, David; Ruiz Ortega, Claudia (World Bank, Washington, DC, 2017)
Financial education programs are increasingly offered by governments, nonprofits, and financial institutions. However, voluntary participation rates in such programs are often very low, posing a severe challenge for randomized experiments attempting to measure their impact. This study uses a large experiment on more than 100,000 credit card clients in Mexico. The study shows how the richness of financial data allows combining nonexperimental methods with the experiment to yield credible measures of impact, even with take-up rates below 1 percent. The findings show that a financial education workshop and personalized coaching result in a higher likelihood of paying credit cards on time, and of making more than the minimum payment, but do not reduce spending, resulting in higher profitability for the bank.